2005
DOI: 10.1111/j.1440-1797.2005.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a non‐vancomycin‐based peritoneal dialysis peritonitis protocol

Abstract: We advocate initial treatment of PD peritonitis with non-vancomycin-based therapy given similar efficacy and the potential for reduction of resistant organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Some previous clinical studies have demonstrated that empirical therapy with first‐generation cephalosporin and gentamicin has a similar efficacy to regimens using second‐line antibiotics (22,23); however, some studies did not have such favorable results (14,24). In this study the efficacy of an empirical regimen with intermittent intraperitoneal first‐generation cephalosporin and gentamicin was poor.…”
Section: Discussionmentioning
confidence: 61%
“…Some previous clinical studies have demonstrated that empirical therapy with first‐generation cephalosporin and gentamicin has a similar efficacy to regimens using second‐line antibiotics (22,23); however, some studies did not have such favorable results (14,24). In this study the efficacy of an empirical regimen with intermittent intraperitoneal first‐generation cephalosporin and gentamicin was poor.…”
Section: Discussionmentioning
confidence: 61%
“…This resolution rate was significantly higher than initial treatment with a first generation cephalosporin plus aminoglycosides (pooled proportion of 66%, 95%CI: 0.57-0.75) from 14 studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] with a total of 1438 total episodes (Figure 1). Initial treatment with ceftazidime plus a glycopeptide also showed a higher resolution rate than a glycopeptide plus aminoglycosides (pooled proportion of 75%, 95%CI: 0.69-0.80), which was used in 16 studies [29][30][31][38][39][40][41][42][43][44][45][46][47][48][49][50] For treatment of episodes due to gram-positive rods, the pooled resolution rate from 13 [23,39,40,48,49,[51][52][53][54][55][56][57][58] studies with a total of 917 episodes was 78% (95%CI: 0.66-0.88) for a glycopeptide, while the rates from five studies [26,…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The only third generation cephalosporin we analyzed Comparisons of episodes due to gram-negative rods showed that the pooled proportion resolution rate from nine studies [39,40,49,57,[60][61][62][63] with a total of 138 episodes was 68% (95%CI: 0.50-0.85) for a quinolone. For ceftazidime, the resolution rate was 61% (95%CI: 0.53-0.70) from three studies [33,63,64] with a total of 117 episodes, and for aminoglycosides the resolution rate was 65% (95%CI: 0.51-0.77) from nine studies [23,26,31,39,40,49,55,60,61] with a total of 211…”
Section: Proportional Meta-analysismentioning
confidence: 99%